Left ventricular ejection fraction of < 20%: Too bad for MitraClip©?. Issue 6 (1st June 2017) - Barth, Sebastian; Hautmann, Martina B.; Kerber, Sebastian; Gietzen, Frank; Reents, Wilko; Zacher, Michael; Halbfass, Philipp; Griese, Daniel P.; Schieffer, Bernhard; Hamm, Karsten
Abstract: Objectives: This study sought to investigate whether the percutaneous mitral regurgitation (MR) reduction with the MitraClip® system in end‐stage heart failure patients with a left ventricular ejection fraction (LVEF) of <20% also effects beneficial outcome or whether the underlying myogenic problem is leading and therefore of prognostic relevance. Backround: The interventional treatment of functional mitral regurgitation (FMR) with the MitraClip ® system could improve the clinical and hemodynamic outcome in patients with severely impaired left ventricular function. Materials and methods: Between 2011 and 2016, a total of 147 patients with FMR were treated with MitraClip ® at our institution. The cohort was divided into two groups: LVEF ≥ 20% ( N  = 126) and <20% ( N  = 21). Follow‐up assessments included exercise capacity, 6‐min walk test, probrain natriuretic peptide‐measurement (ProBNP), echocardiography and right heart catheterization. Only three patients with an LVEF ≥ 20% and one patient with an LVEF < 20% were lost for follow‐up. Results: In the vast majority of patients, a reduction from severe to mild MR was demonstrated with no difference between both groups ( P  = 0.422). At follow‐up, both subgroups experienced similar improvements in exercise capacity and hemodynamics. Patients with an LVEF < 20% were on average 5.8 years younger, while mortality rates were comparable in both groups ( P  = 0.760). Conclusion: By careful selection, even patients in the end stage of advanced LV dysfunction as the result of the underlying myogenic problem and the additional harmful effects of the high volume loading due to the FMR can exhibit significant clinical and hemodynamic improvement after MitraClip © therapy.